Consecutive Sides & Height

A triangle has consecutive side and height lengths for some integer n n , as shown above.

What is its perimeter?


The answer is 42.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Stephen Mellor
Jun 12, 2018

Equating Heron's Formula with the standard 1 2 b h \frac12bh formula for the area of the triangle we get: 1 4 ( a + b + c ) ( a + b c ) ( a b + c ) ( a + b + c ) = 1 2 × Base × Perpendicular height \frac14 \sqrt{(a+b+c)(a+b-c)(a-b+c)(-a+b+c)} = \frac12 \times \text{Base} \times \text{Perpendicular height} 1 4 ( 3 n + 6 ) ( n ) ( n + 4 ) ( n + 2 ) = 1 2 × ( n + 2 ) × ( n ) \frac14 \sqrt{(3n + 6)(n)(n + 4)(n + 2)} = \frac12 \times (n + 2) \times (n) ( 3 n + 6 ) ( n ) ( n + 4 ) ( n + 2 ) = 2 × ( n + 2 ) × ( n ) \sqrt{(3n + 6)(n)(n + 4)(n + 2)} = 2 \times (n + 2) \times (n) ( 3 n + 6 ) ( n ) ( n + 4 ) ( n + 2 ) = 4 × ( n + 2 ) × ( n ) × ( n + 2 ) × ( n ) (3n + 6)(n)(n + 4)(n + 2) = 4 \times (n + 2) \times (n) \times (n+2) \times (n) 3 ( n + 2 ) ( n + 4 ) = 4 × ( n + 2 ) × ( n ) 3(n + 2)(n + 4) = 4 \times (n + 2) \times (n) 3 ( n + 4 ) = 4 n 3(n + 4) = 4n n = 12 \boxed{n = 12} (Notice that we can definitely cancel terms as above, since all of the factors are positive so not zero)

Therefore, Perimeter = 3 n + 6 = 42 \text{Perimeter} = 3n + 6 = \boxed{42}

Chew-Seong Cheong
Jun 13, 2018

Using Pythagorean theorem, we have:

( n + 1 ) 2 n 2 + ( n + 3 ) 2 n 2 = n + 2 2 n + 1 + 6 n + 9 = n + 2 Squaring both sides 2 n + 1 + 2 ( 2 n + 1 ) ( 6 n + 9 ) + 6 n + 9 = n 2 + 4 n + 4 Rearranging n 2 4 n 6 = 2 ( 2 n + 1 ) ( 6 n + 9 ) Squaring both sides n 4 8 n 3 + 4 n 2 + 48 n + 36 = 48 n 2 + 96 n + 36 n 4 8 n 3 44 n 2 48 n = 0 Since n = 0 is not a solution ( n + 2 ) 2 ( n 12 ) = 0 Since n = 2 is not a solution n = 12 \begin{aligned} \sqrt{(n+1)^2-n^2} + \sqrt{(n+3)^2-n^2} & = n+2 \\ \sqrt{2n+1} + \sqrt{6n+9} & = n+2 & \small \color{#3D99F6} \text{Squaring both sides} \\ 2n+1 + 2\sqrt{(2n+1)(6n+9)} + 6n+9 & = n^2+4n+4 & \small \color{#3D99F6} \text{Rearranging} \\ n^2-4n-6 & = 2\sqrt{(2n+1)(6n+9)} & \small \color{#3D99F6} \text{Squaring both sides} \\ n^4 - 8n^3 + 4n^2 + 48n + 36 & = 48n^2+96n+36 \\ n^4 - 8n^3 - 44n^2 - 48n & = 0 & \small \color{#3D99F6} \text{Since }n=0 \text{ is not a solution} \\ (n+2)^2(n-12) & = 0 & \small \color{#3D99F6} \text{Since }n=-2 \text{ is not a solution} \\ \implies n & = 12 \end{aligned}

Therefore the perimeter is n + 1 + n + 2 + n + 3 = 3 ( 12 ) + 6 = 42 n+1+n+2+n+3 = 3(12)+6 = \boxed{42} .

Edwin Gray
Jun 12, 2018

divide the base into two parts: the left side = x; the right side = n + 2 - x. Then we apply the Pythagorean Theorem to each side, resulting in (1) n^2 + x^2 = (n + 1)^2. (2) n^2 + (n + 2 - x)^2 = ( n + 3)^2 Expanding these equations and substituting x^2 = 2n + 1, we straightforwardly get (3) n - 2 = 2x. Expanding, n^2 - 4n + 4 = 4x^2 =8n + 4. Then n^2 - 12n = 0, or n = 12. The perimeter is then = 13 + 14 + 15 = 42. Ed Gray

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...